Injectable hyaluronate-L- cysteine gel potentiates photothermal therapy in osteosarcoma via vorinostat-copper cell death - Sizhen Wang; Hanzhe Zhang; Tianheng Chen; Weiwei Jiang; Feng Wang; Yuhao Yu; Beibei Guo; Jia Xu; Feng Yang; Qinglin Kang; Zhiqiang Ma (Materials Today Bio)
The prognosis for osteosarcoma patients, a devastating malignancy affecting young individuals, remains grim despite multimodal therapeutic advances. Recently, the advent of cuproptosis, a novel programmed cell death, offers hope in fighting osteosarcoma. In this study, we introduce SAHAm@{[Cu(HA-Cys)2]Cl2}n, an injectable hyaluronate-L-cysteine hydrogel that integrates both copper ions (Cu2+) and vorinostat (SAHA) for the possible therapeutic effect. The Cu2+ targets the TCA cycle, inducing cuproptosis in osteosarcoma cells. While SAHA acts as both a histone deacetylase inhibitor and an ROS generator for eliminating tumor cells. The mechanism involves amplifying FDX-1 expression via SAHA modulation of the TCA cycle, which was an original discovery. Critically, the combined mechanisms and localized injection enables the hydrogel partially eradicating osteosarcoma without metastasis in rats. Therefore, this study advances cuproptosis induced photothermal therapy for promising clinical translations, shedding light on favorable prognosis for osteosarcoma.